Analysis of anthropogenic nitrogen and its influencing factors in Beijing. (20th January 2020) - Zhang, Xiaolin; Zhang, Yan; Fath, Brian D.
Abstract: Human activities have changed the global nitrogen cycle and are continuing to do so at an alarming rate. Cities are particularly important nitrogen sinks due to the concentration of human activities, and have attracted widespread attention. However, researchers disagree about the sink size and the underlying socioeconomic factors. Taking Beijing as an example, we developed an anthropogenic nitrogen index to characterize the sink size and the effects of socioeconomic factors, then we used empirical coefficients for the nitrogen content of materials to calculate the total anthropogenic nitrogen consumption and analyzed its structural characteristics. We used the logarithmic mean divisia index to construct a factor decomposition model and analyze the factors affecting anthropogenic nitrogen consumption and their contribution and direction (promotion or inhibition). Beijing's anthropogenic nitrogen consumption increased from 1995 to 2010 in response to increasing consumption of energy, food, and fertilizer nitrogen. Energy nitrogen accounted for the largest proportion of the total (≥33%) and increased greatly. The proportion of food nitrogen increased from 10% to 21% during the study period. Subsequent decreases in anthropogenic nitrogen mainly resulted from decreased fertilizer nitrogen consumption (to 20% of the total consumption) from 2010 to 2015. Of the influencing factors, the inhibitory effect of material intensity on Beijing's anthropogenic nitrogen consumption increased from 22% to 37% during the study period; the promoting effect of per capita GDP gradually weakened, but its contribution remained >30% of the total. By analyzing the dynamics of Beijing's urban anthropogenic nitrogen consumption, we identified the main socioeconomic drivers, thereby providing scientific support for exploring nitrogen consumption patterns during different urban development stages and for the activities required to regulate nitrogen consumption. Graphical abstract: Image 1 Highlights: Analyzed the variation law of the total amount of anthropogenic nitrogen consumption in Beijing. Analyzed the reasons for the structural changes of anthropogenic nitrogen consumption. Constructed a factor decomposition model of anthropogenic nitrogen consumption in Beijing.